First Things First: Summoning History to the Mission of Healing South African Higher Education - Motlalepula Grace Phalwane; Moagisi Edwin Kagiso Seleka (E-Journal of Humanities, Arts and Social Sciences)
The South African Higher Education landscape is fraught with incidents that require urgent attention, if Higher Education is to be restored to its rightful place in the reinvention and preservation of Africa’s last country to obtain liberation. This study, therefore, provides a bird’s eye view on the history pertinent to diagnosis and healing of this pivotal sector of the country’s educational system. Data for the study were generated through the library and search engines for literature on this field of study. While describing the reality about this sector of education, the authors are of the firm belief that the study will contribute to a deeper understanding of the aetiology necessary to ameliorating the effectiveness and relevance of the country’s higher education system. The findings revealed, among others, the disjuncture between the medieval origins of the modern university and the current state of the South African University with its inevitable neocolonial stage of social change, which is compounded by the historical and current societal problems. The study recommends a more existential and corporate solution to the ills of this education sector, with a renewed sense of patriotism and a conscious existential pursuit of knowledge. It proposes an altered perception and a deliberate reversal of the mental destruction that was cultivated to promote the socially stratified society, as well as a balance between neoliberalism and the love of knowledge for its sake. It is also hoped that the study will raise awareness towards the neglected aspects of social reconstruction caused by long-lasting social conflict.